If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2a + 5) = 0 Reorder the terms: 3(5 + 2a) = 0 (5 * 3 + 2a * 3) = 0 (15 + 6a) = 0 Solving 15 + 6a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 6a = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 6a = 0 + -15 6a = 0 + -15 Combine like terms: 0 + -15 = -15 6a = -15 Divide each side by '6'. a = -2.5 Simplifying a = -2.5
| 8x-30=42 | | 7x^2-15=49+3x^2 | | -6x+25=-8x+3.7 | | 1/2+1/3= | | 4p-16-17p+3= | | hi=ih | | 11x+7=5x-3 | | t-7-4t= | | 187-3x=33x+23 | | 2.7=.3y | | 12-6c=24 | | 10=4+2c | | 8x^2+11=191+3x^2 | | 7+3c=22 | | 25(4+2x)=0 | | 8X^2-30X+13=0 | | 150+12m=630 | | .2x=8.26 | | 2w-w+9=16 | | 2x+39=10x-57 | | 6p-(5p+5)=-8-2(1p+12) | | (5n-8)(n+2)=0 | | 9=2x-1 | | z^2+2iz=1+i | | u-41=52 | | -3x=-11 | | 76-2x=10+16 | | -4=3p-75 | | 8=.05b | | 6m-5=7 | | 0.1666666d+.6666666=0.25(d-2) | | 134-7x=29x+22 |